’Paluma’ guava trees under different cultivation systems, times and intensities of fructification pruning - Serrano, Luiz Augusto Lopes; Marinho, Cláudia Sales; Ronchi, Cláudio Pagotto; Lima, Inorbert de Melo; Martins, Marlon Vagner Valentim; Tardin, Flávio Dessaune (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to evaluate the effects of different fructification pruning times and intensities on the yield and fruit quality of ’Paluma’ guava trees in two cultivation systems, in Pedro Canário, ES, Brazil. The experimental design was a randomized complete blocks in a split split plots scheme. The main plots were the cultivated systems (with and without irrigation), the split plots were the pruning times (November 10, 2005; December 9, 2005; January 13, 2006; and February 10, 2006), and the split split plots were the pruning intensities (heavy, medium and light). Plant yield, number of harvested fruits, and fruits medium weight were higher in irrigated plants. Independently of pruning time, plants subjected to heavy pruning provided the smallest yield and number of fruits per plant, however produced the higher fruit weight. The largest yield and number of fruits per plant occurred in plants subjected to medium and light pruning in February, while higher fruit weight occurred in plants pruned in December, regardless pruning intensity. Total soluble solids, titratable acidity and ratio were not affected by pruning intensity; however, those characteristics were affected by cultivate systems and pruning time.